Rancang Bangun Sistem Satu Data sebagai Strategi Peningkatan Mutu Pendidikan Tinggi di Universitas Mataram - Mohammad Zaenuddin Hamidi; Ahmad Zafrullah Mardiansyah; I Wayan Sudiarta; Halil Akhyar (Jurnal Teknologi Informasi dan Multimedia, 2025)
The quality of higher education greatly depends on the accuracy and consistency of data used in decision making and accreditation processes. At the University of Mataram, various information systems have been developed separately, such as the Academic Information System (SIA), the New Student Admission System (PMB), the Research and Community Service Information System (SIMLITABMAS), and the Lecturer Performance Information System (BKD). However, the lack of integration among these systems has resulted in fragmented data, which is often unsynchronized and complicated the quality reporting process. This study aims to design and develop an integrated information system based on the One Data approach, which consolidates various primary data sources into a centralized platform within the University of Mataram. The advantages of the developed system lie in its direct integration with PDDIKTI, enabling automated data retrieval and submission through the national central system. This research adopts a Research and Development (R&D) approach with a Waterfall based software development method, consisting of the stages of requirement analysis, system design, implementation, testing, and evaluation. The results show that the developed system is able to integrate data from various existing systems and presenting it in a consistent format that is easily accessible by relevant units, with testing results achieving a 100% success rate. The system has been proven to support efficiency in reporting and monitoring processes for higher education quality in a more accurate manner. In conclusion, the One Data system contributes significantly to improve the quality of data governance and quality assurance processes in higher education and can serve as a foundation for the development of a more holistic and sustainable academic data ecosystem.